Constructing the self in language and narrative in the work of Grazia Deledda - Jewell, R (2012)
This thesis examines the presence of modernist ideas regarding identity, language and narrative in the work of the neglected Sardinian author, Grazia Deledda (1871-1936). It has the overall aim of redefining Deledda’s later work as modernist for she has been disregarded by most critics and is generally classed as a minor, veristic writer. Drawing Deledda out of these restricted interpretations, this thesis demonstrates that Deledda straddles two literary modes, for she matures beyond veristic influences and looks forward to modernist ideas, particularly regarding the complex nature of the self. The thesis approaches Deledda from an entirely new perspective in that it focuses upon the crisis of identity in Deledda’s work, and its construction in the narrative of her novels, and its integral relationship with the theme of language. The theoretical framework of Julia Kristeva, Paul Ricoeur and Adriana Cavarero enables an innovative study of identity as a linguistic and narrative construct in Deledda’s work. I maintain that Deledda’s characters construct, control and understand their identities through their application of language or their command of narrative perspective, voicing their inner selves through linguistic self-expression. This study engages in a close textual analysis of three of Deledda’s key texts. La madre (1920) and Il segreto dell'uomo solitario (1921) illustrate Deledda’s movement away from verismo. Their protagonists suffer a crisis of identity which is bound up in linguistic expression and/or narrative control. Cosima (1937), which is Deledda’s most autobiographical text, displays the author’s close affinity with her writing. Creating a fiction of her own life, Deledda becomes both narrator and protagonist, self and other in the exploration of her own identity, which is integrally connected to the act of writing. The very composition of this text demonstrates the construction of identity in language and narrative which is illustrated within Deledda’s other works.